2012
DOI: 10.1016/j.jmaa.2012.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability analysis of symmetric periodic simultaneous binary collision orbits in the planar pairwise symmetric four-body problem

Abstract: We apply the symmetry reduction method of Roberts to numerically analyze the linear stability of a one-parameter family of symmetric periodic orbits with regularizable simultaneous binary collisions in the planar pairwise symmetric four-body problem with a mass m ∈ (0, 1] as the parameter. This reduces the linear stability analysis to the computation of two eigenvalues of a 3 × 3 matrix for each m ∈ (0, 1] obtained from numerical integration of the linearized regularized equations along only the first one-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The orbit was shown to be linearly stable in [4]. It was later shown that this orbit could be extended to symmetric masses in [2] (see also [3]), and linear stability for this extension was shown for an interval of certain mass ratios in [1].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The orbit was shown to be linearly stable in [4]. It was later shown that this orbit could be extended to symmetric masses in [2] (see also [3]), and linear stability for this extension was shown for an interval of certain mass ratios in [1].…”
Section: Introductionmentioning
confidence: 91%
“…Different choices of Y 0 will give different properties of the monodromy matrix. It is also worth noting that Y 0 is independent of the value of m for this orbit, which is not always true (see [1]. )…”
Section: Again From [14]mentioning
confidence: 97%
See 1 more Smart Citation
“…How close will 2012 DA14 pass by Earth? A mere 17000 miles (27000 km) 4 . In cosmic terms, this close shave of 2012 DA14 with Earth in 2013 is a near-collision motion.…”
Section: Phenomenonmentioning
confidence: 99%
“…Bakker, Ouyang, Yan and Simmons [3] then numerically extended this non-collinear periodic simultaneous binary collision solution to unequal masses 0 < m < 1. In 2012, Bakker, Mancuso, and Simmons [4] have numerically determined that the noncollinear periodic simultaneous binary collision solution is spectrally stable when 0.199 < m < 0.264 and 0.538 < m ≤ 1 and is linearly unstable for the remaining values of m. Long-term numerical integrations of the regularized equations done by Bakker, Ouyang, Yan, and Simmons [3] suggest instability when 0.199 < m < 0.264 and stability when 0.538 < m ≤ 1 in the sense of Definition 1. For these latter values of m could the near-collision solutions in the PPS4BP that look like the non-collinear periodic simultaneous binary collision solution be collision-free and bounded for all time?…”
Section: Pps4bpmentioning
confidence: 99%